Gutzwiller charge phase diagram of cuprates, including electron–phonon coupling effects. (24th February 2015) - Markiewicz, R S; Seibold, G; Lorenzana, J; Bansil, A
Abstract: Besides significant electronic correlations, high-temperature superconductors also show a strong coupling of electrons to a number of lattice modes. Combined with the experimental detection of electronic inhomogeneities and ordering phenomena in many high- T c compounds, these features raise the question as to what extent phonons are involved in the associated instabilities. Here we address this problem based on the Hubbard model including a coupling to phonons in order to capture several salient features of the phase diagram of hole-doped cuprates. Charge degrees of freedom, which are suppressed by the large Hubbard U near half-filling, are found to become active at a fairly low doping level. We find that possible charge order is mainly driven by Fermi surface nesting, with competition between a near- order at low doping and antinodal nesting at higher doping, very similar to the momentum structure of magnetic fluctuations. The resulting nesting vectors are generally consistent with photoemission and tunneling observations, evidence for charge density wave order in YBa2 Cu3 O including Kohn anomalies, and suggestions of competition between one- and two- q -vector nesting.